Grumblebunny - Hartman, Bob.; Clark, David (David Lynn), 1960- (New York : G.P. Putnam's Sons, 2003)
When three sweet rabbits and one ill-tempered one encounter a hungry wolf, they come to appreciate their differences in attitude.
Keywords: Attitude (Psychology) -- Fiction; Rabbits -- Fiction; Wolves -- Fiction